Public sector reform and indigenous entrepreneurship - Sullivan, Ann; Margaritis, Dimitri (International Journal of Entrepreneurial Behavior & Research, 2000)
This paper considers the implications of the liberalization of the New Zealand economy for entrepreneurial development by indigenous New Zealand Maori tribal organizations. Since 1984 the economic objective of the State has been to create a modern market economy free of price distortions, bureaucratic management and government protectionism. One of the State’s responses to enabling tribal organizations to provide for increased self‐determination and to lessen Maori State dependency was to seriously address the issue of compensation to Maori of resources that had been expropriated or confiscated during the past 150 years. While there have been difficulties in reaching agreement on appropriate or adequate allocations of Crown‐owned resources or compensation, the transferal of resources to private (but collective) Maori ownership is now providing a substantial economic base to build corporate and other entrepreneurial activities. It is argued that such willingness and commitment to transfer resources from the State back to the original owners was a manifest outcome of government’s adoption of liberal economic policies.
Keywords: Economics; Policy; Settlements

Kaupapa maori research - Smith, Linda Tuhiwai Te Rina (Reclaiming Indigenous Voice and Vision, 2000)

Options for Constitutional Change - Wickliffe, Caren; Dixon, Matiu (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: constitutional transformation; mātauranga māori; social life and customs; sovereignty; tino rangatiratanga; tāngata whenua

Millenial Thoughts on Māori Development - Henare, Denese (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: crown; development; mātauranga māori; rangatiratanga; social life and customs; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua

Self-Governance - Turia, Tariana (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: mātauranga māori; rangatiratanga; self-governance; social life and customs; tāngata whenua; whangānui iwi

A Traditionalist Approach to Iwi Government - Potiki, Tahu (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: iwi; mātauranga māori; self-governance; social life and customs; te reo māori; tino rangatiratanga; treaty settlements; tāngata whenua

Restoration of the Tribal Collective: Rebuilding Tribal Capacity Alongside Economic Development - White, Paul (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: development; economic development; mātauranga māori; social life and customs; treaty settlements; tāngata whenua

Maori Education Policy In The New Millennium: Political Rationality & Government Mechanisms - Tooley, Christopher W. R. (2000)
This thesis explores the contemporary political rationality and government mechanisms that develop and impact upon educational policy for Maori. In engaging in a critique of political ideology and operational exposition, this thesis examines and discloses the mechanisms and rationalities of government in New Zealand through state policy theory, gender, race and ethnic writings, critical theory and theories of difference. Of significance to this work is the incorporation of Kaupapa Maori theory, which provides a traditional and contemporary insight into Maori views and praxis of emancipation. In realising the central interest and concern of Maori for real and effective intervention to address the crisis of schooling for Maori, analysis in this thesis examines the historical nature of Maori educational policy and critiques the contemporary educational political frameworks of the New Zealand Labour government. Furthermore, this research also examines government official’s perspectives in discussing the primary contemporary political mechanisms and rationalities that operate in controlling and developing educational policy for Maori. It is argued, that although these contemporary policy frameworks, rationalities and mechanisms may appear to be vastly different from historical colonisation and assimilation practices, they are informed by the same underlying structures and are intersected by similar tendencies and movements. In disclosing the perpetuating ethos of state Pakeha dominant interests and the absence of structural and cultural reform from within political educational policy development for Maori, this thesis argues that state initiatives in the new millennium, under the guise of transformation, commitment and hope still remain ineffective and oppressive for Maori.
Keywords: crown policy; education; kaupapa māori; tiriti o waitangi/treaty of waitangi

Ngāti Porou leadership: Rāpata Wahawaha and the politics of conflict: "Kei te ora nei hoki tātou, me tō tātou whenua" - Soutar, Monty (Massey University, 2000)
The primary focus of this thesis is to explore the reasons for Ngati Porou participation in the wars in New Zealand during the 1860s. Early writers sunnised that the alliances between tribes like Ngati Porou, Te Arawa and the lower Whanganui iwi and the settler governnent were due primarily to a sense of loyalty to the crown. Repetition by later historians has reinforced this notion in New Zealand folklore and historiography. While recent retrospective histories reveal a growing awareness that the motivation behind the alliances was more complex, no analysis of tribal motives worthy of the confidence of Maori has yet been recorded. This thesis initially sets out to detennine whether the historical orthodoxy is founded at least for Ngati Porou. It presents evidence showing that significant aspects of the Ngati Porou story have been misunderstood and misrepresented by writers who have been unable to source or who have felt it unnecessary to properly canvass Ngati Porou views and records. To date, tribal historians have on the whole refrained from presenting a tribal perspective, not because the infonllation does not exist, but from a desire to keep such knowledge in the tIibal arena where it is most relevant. Continued irritation, however, caused by historical publications that fall short when trying to comprehend the nature of Maori participation, has resulted in a freeing up of infonnation by those who jealously guard their family 's manuscripts, and others who retain the oral testimonies within the tribe, so that a re examination is made possible. This thesis also generally seeks to link Ngati Porou 's involvement in war with leadership pattems that emerged within the tribe during the period 1865 - 1872, though this dimension of Ngati Porou history is not canvassed exhaustively here. In times of crisis existing leadership patterns were challenged and as often as not new leaders emerged to lead the tribe. Perhaps the finest military leader produced by Ngati Porou during the Hauhau encounters was Major Rapata Wahawaha. His role in shaping Ngati Porou's modern identity is a major theme running throughout this thesis. It is argued that his leadership and philosophy characterised the contribution by Ngari Porou to theatres of war that followed the 1860s. It is proposed that such a contribution was both strategic and calculated to achieve gains for Ngati Porou. Moreover, the wider question is raised: why, since the 1860s, has Ngati Porou been so ready to join the battlefront and to stand alongside the Crown? The thesis contends that far from being motivated solely by loyalty to the Crown, Ngati Porou entered into an alliance with the Crown in order to protect and to advance tribal interests.
Keywords: crown; iwi politics; ngāti porou; rangatiratanga

Exploring personal and political issues of identity for white Māori women. Whakatoro te Torangapu me te Ake o Nga Kaupapa Tuakiri mo nga Wahine Māori Ma - Bevan, Kelly (2000)
Keywords: identity; mana wāhine; wāhine māori